Verifikasi akurasi arah kiblat masjid Ar-Ridlo kota malang berdasarkan implementasi fatwa MUI No. 05 tahun 2010 menggunakan metode google earth, segitiga bola, dan rashdul kiblat - effendy, maidany (Maliki Interdisciplinary Journal, 2025)
Determining the direction of the qibla is part of the requirements for valid worship (prayer) for a Muslim. The issue of the direction of the qibla in Indonesia once caused controversy after the issuance of MUI Fatwa No. 03 of 2010, which stated that the direction of the qibla should face west. However, after astronomical inconsistencies were discovered, the MUI issued Fatwa No. 05 of 2010 revising the qibla direction to northwest with geographical adjustments for each region. This study aims to test the accuracy of the qibla direction of Ar-Ridlo Mosque in Malang City based on the implementation of this fatwa. The study was conducted through a practical approach in the Astronomy course using three methods: Google Earth, spherical triangle formula, and rashdul kiblat (sun shadow). The analysis results indicate that the qibla direction of the mosque is accurate, with a very small angular deviation (less than 1°) from the ideal direction toward the Ka’bah. This finding demonstrates that celestial science-based qibla direction calculation methods are highly effective in ensuring the accuracy of the qibla direction in areas far from Mecca. This study also underscores the importance of scientific verification in the implementation of religious fatwas related to the qibla direction to alleviate public concerns and maintain the sanctity of worship.